The influence of attitude, subjective norm and perceived behavioural control towards intention to comply speed limit among young drivers in Kuala Muda / Nurfaizuha Mustaffa Kamal and Nur Syahidah Khadir@Mat Isa - Khadir@Mat Isa, Nur Syahidah; Mustaffa Kamal, Nurfaizuha (2018)
Road traffic accidents have become a major public health concern in both developed and developing countries alike as they constitute a major cause of fatalities globally (Akaateba & Amoh-Gyimah, 2013; Kaen, 2016; Paris & Broucke, 2008). According to the World Health Organization, road traffic accident has caused nearly 1.2 million dead and many more cases of disabilities in year 2000. In addition, it was estimated that without the effective implementation of efficient countermeasure, an 80% increase in road traffic accident should be expected in low-and-middle-income countries by year 2020 (Akaateba & Amoh-Gyimah, 2013). More surprisingly, road traffic injuries were the most important problem in the global burden of disease and expected to take up the third place in the ranking of disease burden by the year 2020 (Paris & Broucke, 2008).